Scientific Evaluation of Different Methods for the Determination of Yeast Vitality - Müller-Auffermann, Konrad; Hutzler, Mathias; Schneiderbanger, Hubertus; Jacob, Fritz (BrewingScience, 2011)
In this paper, two non standard methods are introduced and described precisely for measuring the vitality of yeast. Both are simple and produce results in a very short time. For the purpose of demonstrating these methods, brewing yeasts were placed under specific types of stress in various situations and compared to yeast not under stress. Their capacity for producing CO2 was measured, and the condition of their cell walls was determined parallel through potentiometric titration. The results show that both of the methods demonstrated in this paper are effective for determining the physiological condition of yeast. Relative to the untreated yeast, the yeast placed under stress produced less CO2 in controlled small-scale fermentation trials. Also, the condition of their cell walls changed, which was made apparent by the volume titrant required in the potentiometric titration. It should also be mentioned, that the trials described here were in fact preliminary trials for establishing the methodology for the respective tests. In a future paper, a further test designed for practical application in the industry includes a measurement of the intracellular pH and fermentation pressure in addition to the other measurements performed here.